Innovative Nanocarriers: Magnetosomes in the Fight against Cancer - Yadav, Shivani; Mishra, Manoj Kumar (Anti-Cancer Agents in Medicinal Chemistry, 2025)
Recent advancements in medication formulations and drug delivery systems over the past two decades have improved patient adherence and pharmacological responses. Efficient, target-specific medication delivery remains challenging, with many current systems designed to minimize drug loss and degradation. Magnetosomes, as nanocarriers, show promise for delivering antibodies, vaccine DNA, and siRNA, enhancing the stability of chemotherapeutics, and enabling targeted delivery to malignant tumors. Targeted drug delivery is crucial in cancer treatment, as anticancer drugs often cannot differentiate between healthy and malignant cells, causing side effects and systemic toxicity. Magnetosome-based drug delivery offers a potential solution, minimizing adverse effects and promoting drug accumulation at the target site. This review covers the design, development, and advancements in magnetosome-based drug delivery for cancer therapy.
Keywords: Magnetosomes